2021
DOI: 10.1016/j.jbc.2021.101398
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthases 1 and 2 exhibit phosphatidylcholine phospholipase C activity

Abstract: Many studies have confirmed the enzymatic activity of a mammalian phosphatidylcholine (PC) phospholipase C (PLC) (PC-PLC), which produces diacylglycerol (DAG) and phosphocholine through the hydrolysis of PC in the absence of ceramide. However, the protein(s) responsible for this activity have never yet been identified. Based on the fact that tricyclodecan-9-yl-potassium xanthate can inhibit both PC-PLC and sphingomyelin synthase (SMS) activities, and SMS1 and SMS2 have a conserved catalytic domain that could m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Next, we utilized the dKO and the tKO mice on chow diet to perform the rest of the experiments. We measured different lipid levels in the liver of the dKO and the tKO mice and confirmed that there were no differences in sphingomyelin and ceramide ( 9 ) ( Fig. S5 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Next, we utilized the dKO and the tKO mice on chow diet to perform the rest of the experiments. We measured different lipid levels in the liver of the dKO and the tKO mice and confirmed that there were no differences in sphingomyelin and ceramide ( 9 ) ( Fig. S5 ).…”
Section: Resultssupporting
confidence: 55%
“…We and others found that SMSr has PLC activity ( 6 , 8 ) and specifically hydrolyzes PE, making it a phosphatidylethanolamine PLC (PE-PLC) ( 6 ). We also found that SMS1 and SMS2 are two phosphatidylcholine (PC)-PLCs ( 9 ). Given the fact that ( 10 , 11 , 12 , 13 ) PC-PLC and phosphatidylinositol (PI)-PLCs ( 14 ) maintain PC and PI levels and regulate many important biological functions, SMSr-mediated PE-PLC activity should have an important biological function.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…During the storage of quinoa, major lipids involved in the glycerophospholipid pathway include PE, PI, PS, and PG. DG could be involved in the synthesis of PE and PC as a lipid anchor in the presence of the corresponding phosphotransferases, while phospholipase C catalyzes the hydrolysis of PC and PE for the synthesis of DG [40]. In addition, lysophospholipid (LPC and LPE) could be generated via the cleavage of glycerophospholipid (PC and PE) molecules by phospholipase A1 or phospholipase A2, whereas lysophospholipid and acyl-coenzyme A could form glycerophospholipid in the presence of lysophospholipid acyltransferase.…”
Section: Lipid Metabolism Pathways During Quinoa Storagementioning
confidence: 99%
“…Most notably, the genetic sequence of the mammalian PC-PLC has not yet been unambiguously identified. Recently, sphingomyelin synthases 1 and 2 were shown to exhibit PC-PLC-like activity [3], and are required for sphingomyelin homeostasis and growth in human HeLa cancer cells [4]. Thus, it is plausible that other enzymes could mimic PC-PLC activity (moonlighting function).…”
Section: Introductionmentioning
confidence: 99%